PERAN HUKUM DALAM PENCEGAHAN PERKAWINAN DINI SEBAGAI UPAYA PENURUNAN ANGKA STUNTING DI DESA JANAPRIA KECAMATAN JANAPRIA KABUPATEN LOMBOK TENGAH - Lestari, B. Farhana Kurnia; Ferianto, Ferianto; Kusnowo, Syahroni Bayu; Indrawati, Yuni (Jurnal Abdi Insani, 2025)
Early marriage is a contributing factor to stunting, which remains a serious problem in Indonesia, including in Janapria Village, Janapria District, Central Lombok Regency. This community service activity aims to increase community understanding, particularly among adolescents and parents, regarding the dangers of early marriage and its link to stunting. The activity method involved initial observation, legal counseling regarding the minimum age for marriage in accordance with Law of the Republic of Indonesia Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage, nutrition counseling, and interactive discussions. Evaluation included pre- and post-tests, along with feedback from participants. The results of the activity showed an increase in junior high and high school students' understanding of the minimum age for marriage, as well as an increase in housewives' awareness of the role of balanced nutrition and the age of marriage in preventing stunting in Janapria Village, Janapria District, Central Lombok Regency. Participants' enthusiasm was evident in their active participation in discussions, Q&A sessions, and practical sessions on preparing balanced nutritional menus. The conclusion of this activity is that legal socialization and nutrition counseling contribute to increasing public understanding of law and health so that it can become a preventive strategy in reducing the number of early marriages and stunting in Janapria Village.